The Caring Transformation of National Education: Opportunities, Challenges, and Changes (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The COVID-19 pandemic has profoundly impacted all aspects of national education. It has not only highlighted the inadequacies of existing care arrangements but also spurred new care demands. Policymakers and educational institutions increasingly recognize the need to more effectively understand and support the well-being of their domestic students and provide them with more comprehensive care. This paper draws on theories of social material care to explore the possibility of using care as a guiding principle to steer national education in a more productive direction. The core argument is that a focus on care is crucial for promoting the well-being of international students and creating a more effective institutional environment for attracting, retaining, and supporting them. Furthermore, it is essential for redefining and achieving the grand goals of national education itself. This paper demonstrates these points through three "drafts," illustrating how a focus on care can reshape international education policy and institutional support and point to new directions for research on international student mobility.